Functional outcomes and cost-efficiency of specialist in-patient rehabilitation following spinal cord injury: a multi-centre national cohort analysis from the UK Rehabilitation Outcomes Collaborative (UKROC). Issue 19 (11th September 2022) - Turner-Stokes, Lynne; Lafeuillee, Gisele; Francis, Richard; Nayar, Meenakshi; Nair, Ajoy
Abstract: Purpose: To evaluate functional outcomes, care needs and cost-efficiency of specialist rehabilitation for a multi-centre cohort of inpatients with spinal cord injury (SCI)-comparison based on age and aetiology. Methods and materials: Retrospective analysis of prospectively collected data from the UK Rehabilitation Outcomes Collaborative (UKROC) national clinical database from 2012-2019. Adults with SCI admitted for a rehabilitation programme in levels 1 and 2 specialist rehabilitation Units in England, were included if they had valid UK Functional Assessment Measure (UK FIM + FAM) and Northwick Park Dependency Scale (NPDS) scores recorded on admission and discharge ( n  = 2506 of 3321 admissions). Results: Approximately 425 patients were admitted yearly. 1344(56%) patients were under 65. 736(29%) had traumatic aetiology. Older and Traumatic SCI patients were more likely to have cervical cord damage ( X 2, p  < 0.001). There was a significant improvement in all parameters of functional independence (UK FIM + FAM) ( p  < 0.001), with the reduction in dependency and care costs (NPDS/NPCNA) ( p  < 0.001). 1817(72.5%) patients were discharged home. Mean care-costs savings were £25 500/year per patient. Year-on-year trends showed admissions with increasing age, higher complexity and dependency with corresponding increasing episode costs (ANOVA p  < 0.001). However, the time taken to offset the cost of rehabilitation did not change significantly (ANOVA p  = 0.57). Conclusions: Specialist rehabilitation services provide effective and cost-efficient rehabilitation for patients with spinal cord injury. Implications for Rehabilitation: Approximately a third of patients who access specialist inpatient rehabilitation following spinal cord injury (SCI) in England are managed in the Specialist Level 1 and 2 neuro-rehabilitation units, rather than in the eight designated national SCI Centres. Despite admitting progressively more complex and dependent patients over eight years, these specialist rehabilitation units continue to provide highly cost-efficient care. The mean annual savings amount to £25, 500 per patient. With a mean admission rate of 425 patients, this would generate total savings in excess of £10 million per year for the cohort. Specialist rehabilitation services play an important, but under-recognised, role in the spinal cord injury care pathway.